Fluid power design handbook - Yeaple, Franklin D. (Marcel Dekker, 1996)
Maintaining and enhancing the high standards and excellent features that made the previous editions so popular, this book presents engineering and application information to incorporate, control, predict, and measure the performance of all fluid power components in hydraulic or pneumatic systems. Detailing developments in the ongoing "electronic revolution" of fluid power control, the third edition offers new and enlarged coverage of microprocessor control, "smart" actuators, virtual displays, position sensors, computer-aided design, performance testing, noise reduction, on-screen simulation of complex branch-flow networks, important engineering terms and conversion units, and more.